Kara kuvvetleri orta dereceli askeri lise öğrencilerinin coğrafya dersine ilişkin tutumları - Özkılıç, Dilek Yıldızhan (My University, 2003)
With this research students' attitudes to geography courses at Military High Schools under the Land Forces Commandership were studied and tried to find out wether their attitudes are distinct at different schools. Sampling of the research were constituted by 79 students chosen from the 2nd classes of İstanbul Kuleli Military High School, İzmir Maltepe Military High School and Bursa Işıklar Military High School. In order to be able to determine the attitudes of Military High Schools' students to geography courses, the researcher, with the advises of academicians, used a questionair consisting of 21 questions. The one-way variance analysis (ANOVA) was used for the analysis of the data and the Tukey-HSD multiple comparison test for the determination of meaningful differences among the subject schools. Findings of the resears would be summarized as follows; Students of Military High Schools are interested in very much with their environs and they show a positive attitude to watch documentaries, VCDs and CDs and play computer games prepared in Geography. They are affirmative with feeling pleasure and fun during the study of the course. They are of the opinion that geography courses are very important and useful. They also, with a very high majority, show positive attitude other publications like periodicals written on geography.
Keywords: Askeri eğitim; Askeri Eğitim _Türkiye; Askerlik bilimi